BUILDING PSYCHOLOGICAL RESILIENCE AND OVERCOMING ANXIETY OF SPEAKING THROUGH A CURRENT HUMANISTIC PEDAGOGICAL APPROACH IN PANDANSARI VILLAGE - Firdiony Nur Azizah; Chindy Hanggara Rosa Indah (Jurnal Dremi (Demi Pengabdi Masyarakat), 2026)
The most difficult aspect of learning a foreign language for children in rural settings is typically their fear, anxiety, and emotional instability when confronted with a new environment. This participatory action research (*Contemporary Participatory Action Research*) was conducted through the Potential-Based Community Service (PMBP) program in Pandansari Village, Poncokusumo Subdistrict, Malang Regency to investigate the effectiveness of contemporary educational psychology interventions in alleviating these learning fears. The program included 50 students from SDN Pandansari 2 and 95 students from MA Al-Hidayah, who went through a cycle of planning, action, observation, and deep reflection. According to *Complex Dynamic Systems Theory* (CDST) and the *Acceptance and Commitment Therapy* (ACT) paradigm, the solution involved changing rigid classrooms into friendly, accepting settings (*English Café* and a *gamified learning* ecosystem). The findings revealed that teenagers' courage to speak up increased, as did their intrinsic motivation and future orientation. Meanwhile, a review of the research team's psychological burden suggests using an integrated academic calendar to avoid extreme mental tiredness.